2006
DOI: 10.1590/s1517-83822006000300015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and stability of extracellular alkaline proteases from halophilic and alkaliphilic bacteria isolated from saline habitat of coastal Gujarat, India

Abstract: The present study deals with the isolation and characterization of the moderately halophilic-alkaliphilic bacteria from a saline habitat in western India. Eight different bacterial strains were isolated using enrichment techniques at 20% (w/v) NaCl and pH 10. The isolates exhibited diversity towards gram ' s reaction, colony and cell morphology. They were able to grow and produce alkaline protease over a broad range of NaCl, 5-20% (w/v) and pH, 8-10. None of the isolates could grow at pH 7, and one could not g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…The optimum production (190 U/mL) was evident during stationary phase at 56-60 h, suggesting the prominent role of this enzyme in both, primary metabolisms and ecological sustenance. Alkaline proteases from other haloalkaliphilic bacteria studied in our group, reflected the optimum production during the late exponential phase and beginning of the stationary phase [22][23][24]. Interestingly, the enzyme production from S-20-9 was rapidly declined after reaching to optimal level; nevertheless, the production was quite stable up to 104 h (Fig.…”
Section: Growth Kinetics and Protease Productionmentioning
confidence: 76%
See 1 more Smart Citation
“…The optimum production (190 U/mL) was evident during stationary phase at 56-60 h, suggesting the prominent role of this enzyme in both, primary metabolisms and ecological sustenance. Alkaline proteases from other haloalkaliphilic bacteria studied in our group, reflected the optimum production during the late exponential phase and beginning of the stationary phase [22][23][24]. Interestingly, the enzyme production from S-20-9 was rapidly declined after reaching to optimal level; nevertheless, the production was quite stable up to 104 h (Fig.…”
Section: Growth Kinetics and Protease Productionmentioning
confidence: 76%
“…So far, alkaline proteases from halophiles and haloalkaliphiles have been relatively less explored compared to alkaliphiles. However, as revealed from the recent literature [14][15][16][17][18][19][20] and our own studies [21][22][23][24][25], the proteases are wide spread among the haloalkaliphiles and many of them possess the potential that can be novel for biotechnological applications. In order to obtain commercially viable yields, it is essential to optimize fermentation media for the growth and protease production.…”
Section: Introductionmentioning
confidence: 99%
“…2). Alkaline proteases from some other organisms have also displayed the similar pH range; 9-11 [2,9,16,40]. However, the studies on pH stability of AH-6 protease demonstrated a relatively different pattern than the activity profile.…”
Section: Enzyme Purification By Hydrophobic Interaction Chromatographymentioning
confidence: 99%
“…While proteolytic enzymes are reported from halo-neutrophilic bacteria, alkaline proteases from haloalkaliphiles have rarely been investigated [12,17,22,41,51]. We have been involved with the screening and characterization of alkaline proteases from haloalkaliphiles [9,19,27,39,40]. Enzymes derived from these bacteria are potential biocatalysts due to their optimal activities under the conditions of high salt, surfactants, high temperature and alkaline pH [34], whereas the mesophilic counter parts fail to act under similar conditions [55].…”
Section: Introductionmentioning
confidence: 99%
“…Waktu produksi optimum protease terjadi pada fase eksponensial akhir dari kurva pertumbuhan isolat bakteri Salmonella sp. Menurut Dodia et al (2006) waktu produksi optimum protease alkalin dari isolat bakteri S 5 yang diisolasi dari Coastal Gujarat, India juga terjadi pada akhir fase eksponensial.…”
Section: Penentuan Waktu Produksi Optimum Enzim Protease Dan Kurva Peunclassified